Educative Value Analysis in The Film “Orang Kaya Baru” - Hana Zhafira Maulita; Marudut Bernadtua Simanjuntak (Lembaga Pengembangan Kinerja Dosen, 2022)
The main problem in this research is to analyze an educational value in the film